A ten-year follow-up of criminality in Stockholm mental patients. New evidence for a relation between mental disorder and crime - Belfrage, Henrik (The British journal of criminology, 1998)
One thousand and fifty-six mental patients with the diagnosis of schizophrenia, affective psychosis or paranoia, who were discharged from mental hospitals in Stockholm in 1986 were followed up ten years later. The result is an over-representation of criminality among these patients. Of those who were 40 years old or younger at the time of discharge, nearly 40 per cent had a criminal record as compared to less than 10 per cent of the general public. The most frequently occurring crimes are violent crimes. It is stressed that the figures presented represent only an absolute minimum, since several sources of error have been identified, which are discussed in detail